2020
DOI: 10.1007/s10147-020-01692-z
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter retrospective study of nivolumab monotherapy in previously treated metastatic renal cell carcinoma patients: interim analysis of Japanese real-world data

Abstract: Background In a phase III clinical trial, CheckMate 025, treatment of metastatic renal cell carcinoma (mRCC) with nivolumab demonstrated superior efficacy over everolimus. However, as the clinical trial excluded patients with specific complications and poor performance status (PS), the effectiveness and safety of nivolumab in clinical practice, in which patients with various clinical complications are treated, is unclear. This study explored real-world nivolumab treatment in Japanese mRCC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 18 publications
3
33
1
Order By: Relevance
“…In this study, the median progression‐free survival (PFS) was 7.2 (95% confidence interval [CI]: 5.1‐14.3) months, and the median overall survival (OS) after ICI therapy was 22.9 (95% CI: 16.3‐NA) months. The 1‐year OS rate (n = 27) was 80.4% (95% CI: 63.2‐90.2), which was similar to that obtained in a Japanese multi‐institutional study 20 . In the Kaplan‐Meier analysis of PFS according to ICI treatment, the TDO expression level 3‐4 group had significantly poorer prognoses (median PFS, 4.9 months; 95% CI: 1.4‐5.4) than the TDO expression level 1‐2 group (median PFS, 14.3 months; 95% CI: 7.0‐NA; P < .001; Figure 5A).…”
Section: Resultssupporting
confidence: 82%
“…In this study, the median progression‐free survival (PFS) was 7.2 (95% confidence interval [CI]: 5.1‐14.3) months, and the median overall survival (OS) after ICI therapy was 22.9 (95% CI: 16.3‐NA) months. The 1‐year OS rate (n = 27) was 80.4% (95% CI: 63.2‐90.2), which was similar to that obtained in a Japanese multi‐institutional study 20 . In the Kaplan‐Meier analysis of PFS according to ICI treatment, the TDO expression level 3‐4 group had significantly poorer prognoses (median PFS, 4.9 months; 95% CI: 1.4‐5.4) than the TDO expression level 1‐2 group (median PFS, 14.3 months; 95% CI: 7.0‐NA; P < .001; Figure 5A).…”
Section: Resultssupporting
confidence: 82%
“…Recently, Hinata et al (21) reported the real-world prognostic outcomes of a wide range of Japanese patients with mRCC receiving nivolumab, and they were shown to be slightly poorer compared with those in the present study. The present study excluded patients who were diagnosed with non-clear cell RCC and/or received >3 molecular-targeted agents prior to the introduction of nivolumab in order to minimize the risk of bias induced by the heterogeneous characteristics of the included patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Patients included in this analysis had a median duration of treatment (DOT) of 5. 15 Several reasons may account for these differences. First, our population is smaller, which may increase the risk of selection bias; second, 4.26% of our patients were treated beyond progression if a clinical benefit was documented; third, 65% of patients had a treatment escalation, i.e.…”
Section: Discussionmentioning
confidence: 99%